Adoption analysis of agricultural technologies in the semiarid northern Ethiopia: A panel data analysis - Menasbo Gebru; Stein Terje Holden; Frode Alfnes (Agricultural and Food Economics, 2021)
Agricultural technology change is required in developing countries to increase the robustness to climate-related variability, feed a growing population, and create opportunities for market-oriented production. This study investigates technological change in the form of adoption of improved wheat, drought-tolerant teff, and cash crops in the semiarid Tigray region in northern Ethiopia. We analyze three rounds of panel data collected from smallholder farms in 2005/2006, 2009/2010, and 2014/2015 with a total sample of 1269 households. Double-hurdle models are used to assess how the likelihood (first hurdle) and intensity of technology adoption (second hurdle) are affected by demographic, weather, and market factors. The results indicate that few smallholders have adopted the new crops; those that have adopted the crops only plant small shares of their land with the new crops, and that there has been only a small increase in adoption over the 10-year period. Furthermore, we found that high population density is positively associated with the adoption of improved wheat, and previous period's rainfall is positively associated with the adoption of drought-tolerant teff. The adoption of cash crops is positively associated with landholding size and access to irrigation. The policy implications of these results are that the government should increase the improved wheat diffusion efforts in less dense population areas, make sure that drought-tolerant teff seed is available and affordable after droughts, and promote irrigation infrastructure for production of cash crops.
Keywords: O33; Q12; Q16; R34; 330; Climate risk; Double-hurdle; New crop varieties; Northern Ethiopia; Semiarid areas